the PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN RUMAH BATIK KOMAR - Hasya, Sekar Triaghnia; Luturlean, Bachruddin Saleh (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
The traditional batik craft which is now spread throughout Indonesia is a richness of Indonesian culture that should not be left behind and forgotten, especially for all Indonesian people in general. One of the factors that can encourage increased productivity of human resources is efforts to increase work motivation, such as fulfilling both external and internal needs. This research aims to find out whether work motivation and the physical work environment have an influence on the performance of the employees of Rumah Batik Komar. In this research the author used quantitative methods and used descriptive analysis. This research uses multiple linear regression analysis techniques and sampling using probability sampling techniques using simple random sampling. The results of multiple linear regression analysis research show that work motivation variables (X1) and physical work environment (X2) on employee performance (Y) have a significant influence